INFLUENCE AUDITOR'S ORGANIZATIONAL COMMITMENT AND WORK STRESS ON AUDITOR'S PERFORMANCE AND LOCUS OF CONTROL - Zalikha; Nurjannah; Mulyadi; Lakharis Inuzula (IAIN Lhokseumawe, 2022)
The purpose of this study is to explain the effect of organizational commitment and work stress on auditor performance and the impact on the locus of control on the internal auditors of PT. Bank Aceh Syariah Aceh’s Province. The results of the research must be used in full practically and theoretically, namely the substance in human resource development management, especially the internal auditors of PT. Bank Aceh Syariah Aceh’s Province to improve performance. The research method used is Quantitative Research, with descriptive and verification research. Collecting data through questionnaires with field study techniques, census sampling. Field data collection was carried out in 2022. The statistical analysis technique to test the hypothesis used Moderate Regression Analysis (MRA). The results of the study show that (1) organizational commitment has a positive and significant effect on the performance of the internal auditors of PT. Bank Aceh Syariah of Aceh’s Province. (2) work stress has a negative and significant effect to the performance of the internal auditors PT. Bank Aceh Syariah Aceh’s Province. (3) Locus of control partially has a positive and significant impact on the performance of the internal auditors PT. Bank Aceh Syariah Aceh’s Province. (4) Locus of control strengthens the relationship between organizational commitment and the performance of the internal auditors PT Bank Aceh Syariah of Aceh’s Province. (5) Locus of control strengthens the relationship between work stress and the performance of the internal auditors Bank Aceh Syariah Aceh’s Province.